Exploration of the appropriate recommended nutrient intake of iodine in healthy Chinese women: an iodine balance experiment. Issue 5 (11th December 2018) - Tan, Long; Tian, XiaoXiao; Wang, WenQiang; Guo, XiaoHui; Sang, ZhongNa; Li, Xiang; Zhang, Pan; Sun, Yu; Tang, CaiYun; Xu, Zhen; Shen, Jun; Zhang, WanQi
Abstract: There is a dearth of data on the iodine balance studies of Chinese population. In the present study, we aimed to explore the appropriate recommended nutrient intake (RNI) of iodine based on healthy Chinese women. A 4-week study was conducted in twenty-five Chinese euthyroid women. Uniform diets with different iodine contents were provided in two different periods, in which non-iodised salt was given in the first 3 weeks, followed by 1 week of iodised salt administration. The total iodine intake from diet, water and air as well as the total iodine excretion through urine, faeces and respiration were monitored and determined. The sweat iodine loss was also considered. Moreover, the regression curve model was established between the 24 h iodine intake and 24 h iodine excretion. The 24 h iodine intake in the two periods was 194·8 (sd 62·9) and 487·1 (sd 177·3) μg/d, respectively. The 24 h iodine excretion was 130·9 (sd 39·5) and 265·4 (sd 71·8) μg/d, respectively. Both 24 h iodine intake and 24 h iodine excretion of the two periods were significantly different (all P <0·05). The iodised salt contributed approximately 62·7 % of the total daily iodine intake. Moreover, 92·3 % (277/300) of samples were in positive balance, while twenty-three cases were in negative balance. Our data show that the estimated average requirement for iodine was 110·5 μg/d. Therefore, the RNI for iodine to non-pregnant, non-lactating Chinese women was 154·7 μg/d.